Cross-Cultural Evaluation of Associative Memory Intervention Using Virtual Reality...20th Health Informatics Meets Digital Health Conference, May 12–13, 2026, Vienna, Austria - AMPOFO, Prince; VITALI, Andrea; MORGANTI, Francesca; REGAZZONI, Daniele; DOVIE, Delali A.; OSAFO, Joseph; RIZZI, Caterina (Studies in Health Technology & Informatics, 2026)
Background: Associative memory is essential for daily functioning; however, VR interventions in this domain are limited. Objectives: The present study examined associative memory in different modalities and investigated the effects of culture on performance and response time in a virtual environment. Methods: Twenty-two healthy younger adults from Italy and Ghana (ages 18 - 26) completed eight training trial sessions on object-name matching and object-sound matching tasks in a virtual environment. Results: Performance improved progressively across trials in both tasks, with greater accuracy and faster response times in the objectname task than in the object-sound task. Cross-cultural comparisons revealed no significant performance differences between the Ghanaians and Italians. However, the Italians completed both tasks significantly faster than the Ghanaians. Conclusion: The findings of the present study indicate that associative memory is culturally invariant, whereas response-time differences may reflect cultural influences on processing strategies. Overall, this study supports the use of VR as a culturally adaptable platform for associative memory assessment and training.